Anthelmintic drug actions in resistant and susceptible C. elegans revealed by electrophysiological recordings in a multichannel microfluidic device - Weeks, Janis C. (Int J Parasitol Drugs Drug Resist, 2018)
Many anthelmintic drugs used to treat parasitic nematode infections target proteins that regulate electrical activity of neurons and muscles: ion channels (ICs) and neurotransmitter receptors (NTRs). Perturbation of IC/NTR function disrupts worm behavior and can lead to paralysis, starvation, immune attack and expulsion. Limitations of current anthelmintics include a limited spectrum of activity across species and the threat of drug resistance, highlighting the need for new drugs for human and veterinary medicine. Although ICs/NTRs are valuable anthelmintic targets, electrophysiological recordings are not commonly included in drug development pipelines. We designed a medium-throughput platform for recording electropharyngeograms (EPGs)—the electrical signals emitted by muscles and neurons of the pharynx during pharyngeal pumping (feeding)—in Caenorhabditis elegans and parasitic nematodes. The current study in C. elegans expands previous work in several ways. Detecting anthelmintic bioactivity in drugs, compounds or natural products requires robust, sustained pharyngeal pumping under baseline conditions. We generated concentration-response curves for stimulating pumping by perfusing 8-channel microfluidic devices (chips) with the neuromodulator serotonin, or with E. coli bacteria (C. elegans’ food in the laboratory). Worm orientation in the chip (head-first vs. tail-first) affected the response to E. coli but not to serotonin. Using a panel of anthelmintics—ivermectin, levamisole and piperazine—targeting different ICs/NTRs, we determined the effects of concentration and treatment duration on EPG activity, and successfully distinguished control (N2) and drug-resistant worms (avr-14; avr-15; glc-1, unc-38 and unc-49). EPG recordings detected anthelmintic activity of drugs that target ICs/NTRs located in the pharynx as well as at extra-pharyngeal sites. A bus-8 mutant with enhanced permeability was more sensitive than controls to drug treatment. These results provide a useful framework for investigators who would like to more easily incorporate electrophysiology as a routine component of their anthelmintic research workflow.